APPRAISAL OF THE WIND POTENTIAL AS AN ALTERNATIVE SOURCE OF ENERGY IN KASHERE, GOMBE STATE, NIGERIA. - Ohakwere-Eze, Michael; Udo, A. A.; Nosike, C. V.; Alhassan, A.; Adamu, M. K. (FUDMA JOURNAL OF SCIENCES, 2020)
The sources of energy we use in our day-day activities contributes significantly to the alarming global warming which the world is currently experiencing. A technical solution to the menace of an environmental friendly, sustainable and reliable energy is the peak of this research. Wind speed data from 2014 to 2017 measured at a height of 2 m were analyzed using the Weibull’s distribution method. The results show that all through the studied years and seasons, the mean wind speed distribution for the rainy season is significantly stable as seen from the K-values. However, the dry season has the highest K-value of 2.08 signifying more stable winds during the season. The monthly averages, computed for height of 60 m above ground level ranges between 2.15 m/s and 6.42 m/s with the maximum wind speed in June while the minimum wind speed occurred in September. This implies that the wind velocity of the study area tends to be lower during the end of the rainy season. Nevertheless, the deviation in the mean wind speed was not significant, as such wind energy can serve as a reliable energy source for the area hence could be harvested
Keywords: Renewable energy, wind energy, weibull distribution, wind speed